Work frequency band and BS spacing optimization of CBTC in 1.8 GHz under identical and adjacent interferences - Ruichen XU; Dahui ZHAN; Ji FANG; Hao DU; Huasheng LI (Dianxin kexue)
Communication based train control system (CBTC) is assigned in 2.4 GHz unlicensed band,and is easily interfered by Wi-Fi,which caused several emergency brake accidents in Shenzhen and Beijing.Under identical and adjacent interferences from existing systems,choose appropriate frequency band,working bandwidth and station spacing to improve throughput and emergency brake probability for CBTC system is necessary.Firstly,interference research scenarios were analyzed.Then,safety isolation between CBTC train and interferes through deterministic calculation was calculated.Afterwards,appropriate working bandwidth,frequency band and BS spacing was obtained by comparing system level simulation results,including throughput and emergency brake probability,in different conditions.